PHENOTYPE AND FUNCTIONS OF DENDRITIC CELLS IN PATIENTS WITH CHRONIC VIRAL HEPATITIS - O. Yu. Leplina; M. A. Tikhonova; A. E. Borisova; N. M. Starostina; A. A. Ostanin; E. R. Chernykh; V. A. Kozlov (Медицинская иммунология, 2014)
Abstract. Phenotypic and functional features of IFNα-induced dendritic cells (DCs) were studied in patients with chronic viral hepatitis B and C (HBV and HCV), and in cases with hepatitis-related liver cirrhosis (LC). It was shown that DCs are characterized by delayed differentiation/maturation which was more pronounced in HCV patients, as well as in all patients with LC, regardless of virus type. DCs from HBV patients were characterized by increased IFNγ secretion. Transformation of HBV-infection to LC is accompanied by a moderate decrease in IFNγ production, combined with a significantly increased IL-10 secretion. Irrespectively of fibrosis severity, the IFNα-induced DCs of HCV patients displayed active IL-10 synthesis. Moreover, ability of DCs to secrete IFNγ was significantly decreased only in cases of fibrosis-complicated HCV-infection. With respect to TNFα and IL-4 production levels, DCs of the patients were compatibe to normal donor cells, independently on the type of virus, or fibrosis severity. DCs from HBV- and HCV-patients were characterized by intact allostimulatory and Th1/Th2-stimulatory activities in MLC. At the same time, IFNα-induced DCs exhibited suppression of allostimulatory and increase in Th2-polarizing activity upon LC development, both in HBV and HCV patients.